Anticlastogenic properties of methanolic extract of cnestis ferruginea leaves (2006)
The inhibitory activity of methanolic extract of Cnestis ferruginea was investigated in hone marrow cells of mice using micronucleus assay. The mice were fed with the extracts at two different concentrations (100 and 200mg/kg body weight) white control mice were fed with corn oil for six days ad libitum. On the seventh day the mice were administered a single dose of sodium arsenile (2.5mg/kg) and sacrificed after 24hrs. Bone marrow smear were prepared for Observation of claslogenic effect. Results show micronuclei formation in the polychroniatic erythrocyte (PCEs) in the Sodium arsenite treated mice. Claslogenecity induced by sodium arsenile was significantly reduced in mice pretreated with the extract al 100mg/kg body weight while more significant reduction was noted at 200mg/kg body weight. The result indicates a dose dependent relationship of the inhibitory activity of the extract against sodium arsenile induced clastogenecity.